Trust Management for Service-Oriented Environments - Malik, Zaki; Bouguettaya, Athman (Springer US : Imprint: Springer, 2009)
Trust Management for Service-Oriented Environments presents social network-based techniques for establishing trust in decentralized environments. This is one of the first books that provide an overview of trust management for open service-oriented environments. Trust Management for Service-Oriented Environments focuses on peer-to-peer computing (P2P) reputation techniques for establishing trust. This book also covers in-depth analysis of trust management issues in open service-oriented environments, trust models for ad-hoc service composition and evaluation of reputation-based trust models for service oriented environments. Excerpts from Prof. Elisa Bertino's foreword: "This book represents the first comprehensive coverage of the principles, methods and systems for trust management and evaluation in service oriented environments...The central part of the book is devoted to reputation-based approaches to trust. Reputation techniques are the most widely used techniques for assessing whether parties in a distributed open system can be trusted. The book provides a well organized systematic treatment of reputation, by organizing the presentation according a notion of reputation life cycle... This book is an invaluable reference for researchers in academia and industry who are interested in getting acquainted with the foundations of trust for service." Trust Management for Service-Oriented Environments is designed for researchers and practitioners working in the service-oriented computing area. This book is also suitable for advanced-level students in computer science.